Robust room temperature valley Hall effect of interlayer excitons - Huang, Zumeng (2021)
The Berry curvature in the band structure of transition metal dichalcogenides (TMDs) introduces a valley-dependent effective magnetic field, which induces the valley Hall effect (VHE). Similar to the ordinary Hall effect, the VHE spatially separates carriers or excitons, depending on their valley index, and accumulates them at opposite sample edges. The VHE can play a key role in valleytronic devices, but previous observations of the VHE have been limited to cryogenic temperatures. Here, we report a demonstration of the VHE of interlayer excitons in a MoS2/WSe2 heterostructure at room temperature. We monitored the in-plane propagation of interlayer excitons through photoluminescence mapping and observed their spatial separation into two opposite transverse directions that depended on the valley index of the excitons. Our theoretical simulations reproduced the salient features of these observations. Our demonstration of the robust interlayer exciton VHE at room temperature, enabled by their intrinsically long lifetimes, will open up realistic possibilities for the development of opto-valleytronic devices based on TMD heterostructures.